Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2007)
We are happy to present this special issue of the Journal of Engineering Education (JEE) on TQM. We are overwhelmed by the enthusiastic response received from various quarters. Our contributors include teachers, consultants, and serious researchers from all over the country. Due to their support and encouragement, we are coming out with the 9th Special Issue of our Journal on "TQM in Engineering Education".